Non-equilibrium electron and vibrational distributions under nanosecond repetitively pulsed CO discharges and afterglows: I. optically thick plasmas. (13th September 2018) - Pietanza, L D; Colonna, G; Capitelli, M
Abstract: Nanosecond repetitively pulsed (NRP) atmospheric discharges in reacting CO mixtures have been investigated by considering different case studies obtained by changing the interpulse delay time ( t id ) in the range 1–25 μ s and the gas temperature in the range 500–2000 K. Molar fractions of neutral and ionized particles, including free electrons as well as electron energy distribution (eedf) and vibrational distribution (vdf) functions, have been discussed by solving an appropriate Boltzmann equation and a sophisticated state-to-state vibrational kinetics of CO coupled with a simplified plasma-chemistry, describing the most important chemical species including electronic excited states. Large deviations of eedf from the Maxwell distributions are observed, especially at low t id values, as a result of superelastic electronic collisions (SEC) acting in post-discharge and mainly involving CO electronic excited states. Numerous peaks are observed in the eedf because the present study deals with so-called optically thick plasmas when radiative emission is totally reabsorbed. Non-equilibrium vdf are also observed, with plateaux tending to decrease with an increase in gas temperature, which weakens the V–V up pumping mechanism.